1971
DOI: 10.1136/pgmj.47.551.599
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve disease, systemic embolism and anticoagulants

Abstract: Of the 500 cases, 125 (25%) suffered from a systemic embolus. Thirty-seven of these (30%) had more than one embolus, the total number of embolic episodes being 173. Twenty-seven per cent of the group were men and 73% were women. The overall frequency of emboli was 25% for both men and women. Figure 1 shows the age at the time of the first embolus. It is apparent that while the maximum incidence is between the ages of 40 and 50 years, thirty-one of the patients were under the age of 40 and seven were under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

1980
1980
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(46 citation statements)
references
References 14 publications
(11 reference statements)
2
42
0
2
Order By: Relevance
“…40 He confirmed his previous view that "treatment with anticoagulants has significantly improved the prognosis of cerebral embolism in relation to immediate outcome, late survival and recurrence". Also, Fleming and Bailey 48 noted only 5 systemic emboli in their 217 patients treated with long-term anticoagulation, for an embolus rate of 0.8% per patient-treatment year.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…40 He confirmed his previous view that "treatment with anticoagulants has significantly improved the prognosis of cerebral embolism in relation to immediate outcome, late survival and recurrence". Also, Fleming and Bailey 48 noted only 5 systemic emboli in their 217 patients treated with long-term anticoagulation, for an embolus rate of 0.8% per patient-treatment year.…”
Section: Treatmentmentioning
confidence: 99%
“…48 ' 68 Twenty to 70% of these systemic emboli are cerebral, 40% being the average, with the higher figures coming from clinical series. 42 ' "• 69 Though many of the series reported are small and retrospective, it is clear that cerebral embolism is common in patients with RHD, even when they appear to be in a stable sinus rhythm.…”
Section: Source Of Cerebral Embolimentioning
confidence: 99%
“…3,4 Among the potential risk factors for ischemic stroke, the role of an increased atrial size has been controversial, having been supported by some studies [5][6][7][8][9][10] and negated by others. [11][12][13][14][15][16][17][18] Most of these studies, however, were conducted in patients with mitral valve disease or atrial fibrillation, so that the independent contribution of an increased atrial size to the risk of stroke in patients without those conditions was difficult to evaluate. Recently, prospective data from the Framingham study 19 indicated that left atrial enlargement was a risk factor for ischemic stroke only in men and that the association appeared to be at least partially mediated by left ventricular mass.…”
mentioning
confidence: 99%
“…2-4,6-9 Of these risk factors for thrombotic events in AF patients, mitral stenosis is by far the most important. 8 Thus, we have reached the consensus that anticoagulation therapy in mitral stenosis is needed no matter whether the patient has AF or not if that patient has severe mitral stenosis with an enlarged left atrium or a previous history of embolic events. 9 There are several direct oral coagulation factor inhibitors, such as direct thrombin inhibitor and direct Xa inhibitor, registered for the prevention of stroke and systemic embolism in patients with non-valvular AF.…”
Section: Article P 325mentioning
confidence: 99%